2013
DOI: 10.1002/cssc.201300127
|View full text |Cite
|
Sign up to set email alerts
|

Platinum‐ and Membrane‐Free Swiss‐Roll Mixed‐Reactant Alkaline Fuel Cell

Abstract: Eliminating the expensive and failure-prone proton exchange membrane (PEM) together with the platinum-based anode and cathode catalysts would significantly reduce the high capital and operating costs of low-temperature (<373 K) fuel cells. We recently introduced the Swiss-roll mixed-reactant fuel cell (SR-MRFC) concept for borohydride-oxygen alkaline fuel cells. We now present advances in anode electrocatalysis for borohydride electrooxidation through the development of osmium nanoparticulate catalysts support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…As the objective of using a 3D anode such as GF is to increase the available surface area for the biocatalyst attachment, the anode surface activation can be essential for the microbial colonization on this large surface. The surface activation of the carbon substrate can improve the performance significantly through improving the overall hydrophilicity of the graphite material, enhancing the biocompatibility of carbon material as well as facilitating the immobilization of the bacteria, and improving the mass transfer within the porous electrode matrix …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the objective of using a 3D anode such as GF is to increase the available surface area for the biocatalyst attachment, the anode surface activation can be essential for the microbial colonization on this large surface. The surface activation of the carbon substrate can improve the performance significantly through improving the overall hydrophilicity of the graphite material, enhancing the biocompatibility of carbon material as well as facilitating the immobilization of the bacteria, and improving the mass transfer within the porous electrode matrix …”
Section: Resultsmentioning
confidence: 99%
“…The surface activation of the carbon substrate [13,16,[26][27][28] can improve the performance significantly through improving the overall hydrophilicity of the graphite material, [26,28,29] enhancing the biocompatibility of carbon material as well as facilitating the immobilization of the bacteria, [30] and improving the mass transfer within the porous electrode matrix. [31] The Effect Of Anode Surface Area…”
Section: Fpmfc Performance Improvementmentioning
confidence: 99%
“…Notably,H COOHa nd HCOO À can be used as fuel to feed am ixed-reactant fuel cell (MRFC);i nt his versatile fuel cell type,a lso licensed by Mantra Corp., [84a,b] am ixture of fuel ando xidant flows through the membrane-free cell as as ingle stream;t he mixed-feed concepta llowsf or aw ide range of different cell stack designs,s uch as the Swiss-roll MRFC constructionp reviously described by Aziznia, Oloman and Gyenge. [85,86] Finally,H COOH/HCOO À productsc an also be used in the manufacturing industry as buildingb lock for different kind of materials,s uch as rubber, pharmaceuticals,e tc.…”
Section: Pilot Project From Asubsidiary Of Mantra Group:c Ombining Fomentioning
confidence: 99%
“…3 Regarding the discovery of non-Pt based anode catalysts for DBFC, it was shown that Os can act as an efficient electrooxidation catalyst for BH 4 − . [3][4][5][6] Using an amorphous Os thin-film electrode suitable for microfluidic devices, a maximum Os catalyst mass-specific activity of about 1240 A g −1 has been reported. 5 Also, the effectiveness of Os nanostructured extended reaction zone anodes in the "Swiss-roll" mixed reactant DBFC has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…5 Also, the effectiveness of Os nanostructured extended reaction zone anodes in the "Swiss-roll" mixed reactant DBFC has been demonstrated. 6 From a catalytic point of view, borohydride is competitively involved in two reaction types on the anode. One is direct electrooxidation with a theoretical maximum number of electrons exchanged equal to eight:…”
Section: Introductionmentioning
confidence: 99%